Intercultural communication competence scale: invariance and construct validation in Portugal - Gonçalves, Gabriela Maria Ramos (2020)
This article explores the psychometric validation of an Intercultural Communication Competence (ICC) scale. Three studies were performed: (1) psychometric evidence pertaining to the scale’s reliability and factor structure and an analysis of the measurement invariance; (2) assessment of convergent and predictive validity; and (3) analyzes the association between ICC and affective and cognitive dimensions of cultural empathy. A three-factor model with eight items yielded the best fit to the data. The scale showed non-invariance between genders, but proved to be a predictor of intercultural contact. Convergent validity were demonstrated.